Age, Gender and Occupational Profiles of Patients Presented with Unstable Intertrochanteric Fracture (KYLES Type III and IV) (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Unstable Intertrochanteric Fracture (KYLES Type III and IV) can occur in different age group of patients with occupational profiles.Objective: The purpose of the present study was to observe the age, gender and occupational profiles of patients presented with unstable intertrochanteric fracture (KYLES Type III and IV).Methodology: This was a cross-sectional study of patients with intertrochanteric femoral fractures attending at the emergency Department of National Institute of Traumatology and Orthopaedic Rehabilitation (NITOR), Dhaka, Bangladesh during the period of January 2013 to December 2014 for a period of two years. The age, gender and occupational profiles were recorded for this study. All the patients were treated with proximal femoral locking compression plate.Results: Fourteen patients were male and 6 patients were female with the aged of 40 to 80 years and mean age was 67.85±11.30 years who underwent internal fixation with the PF-LCP for proximal femoral fractures were reviewed. Male was predominant than female.Conclusion: In conclusion, most of the patients are elderly people with the male predominance.Journal of National Institute of Neurosciences Bangladesh, July 2024;10(2):94-97